Feasibility Study of Padarangin Cave Slogohimo Wonogiri for Eco-Tourism - Priyono, Kuswaji Dwi (Forum Geografi, 2003)
Area of Karst of mount Sewu in countryside of Padarangin own immeasurable of potency to be developed by besides activity of mining namely the tourism activity. Cave of nature found enable to can be developed as tourism, but date not yet been known how big potency of relevant tourism with the cave.Â In line with the problems, this research aim to provide basic data of potency of cave and assess elegibility of cave. Padarangin for ecotourism in Wonogiri Regeny. Method used by survey of field and interview resident. Result of research indicate that cave of Padarangin have mount of cave at height 848 m msl which relative narrow, chamber horizontal as long as 63,8 m and vertical in 32,5 m. Needed by a special equipment to enter cave with capasities 10 â 15 people once the visit/incoming, owning value of sakral trusted by local society. The cave competent to be developed as tourism object of special enthusasm with visit limited.Â